A marisqueira na cadeia de pesca de Pirambu: as mulheres ficam do lado de lá - Garcia, Hellen Cristina Semeão (2023)
The objective of this research dealt with gender issues, intertwining and intersections between guidelines such as class, race, patriarchy, gender relations and sexism. The field of study was the community of fishermen and women in the municipality of Pirambu, a community that has its cultural and economic practices linked to the maritime space. Thus, the research sought to understand the woman's relationship with the environment and work, within a masculinized space of power. After all, in fishing the man is seen as the provider, the strong guy who goes out in search of supplies, and the woman is reserved for domestic activities, considered more delicate. In this perspective, for the women of that community, the shrimp processing site is intended, as it is a sensitive activity that needs to be carried out very calmly and subtly. The research proposed a path based on women who are crossed by issues such as social organization, class, power systems, patriarchy and race, thus, based on their experiences as fisherwomen, shrimp processors, holders of traditional knowledge, how they relate with these issues was analyzed. For this, the existing layers between these relationships will be presented, in addition to the violence to which these women are exposed in the work environment in a perspective of maintaining their means of subsistence. In this sense, maritime anthropology dialogues with social problems, with an interest in the role of women in the Pirambu fishing community, in the relationship between traditional knowledge, their role in society and the conflicts that emerge from the relationship with artisanal fishing and its social relations . and economic practices.